Taxonomy and classification of cacao - Bhattacharjee, Ranjana; Akoroda, M.O. (Burleigh Dodds Science Publishing Limited, 2018)
Theobroma cacao is one of the most important cash crops in the world and is native to the tropical, humid forests of South America. This chapter discusses its origin and the taxonomy and classification of the varieties of Theobroma. It then reviews the characteristics of the three general groups of Theobroma: criollo, forastero and trinitario.